Peran Micro-Influencer Tiktok sebagai Strategi Public Relations Komunikasi Pemasaran untuk Peningkatan Eksistensi Merk Gulapadi - Anggi Tri Rahmandani; Iis Zilfah Adnan; Muliyati Mat Alim (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to examine the role of TikTok micro-influencers as an effective public relations strategy to enhance the presence of the Gulapadi brand in today's fast-evolving digital era. It combines three important marketing communication approaches—advertising, sales promotion, and social media marketing—to achieve comprehensive and optimal results. A descriptive qualitative method was employed, gathering data through in-depth interviews with four groups of informants: micro-influencers, consumers, employees, and digital marketing experts. The findings demonstrate that micro-influencers successfully deliver promotional content in a manner that is not only engaging but also credible, which helps increase consumers' purchase intentions. Additionally, two-way interactions through comments and electronic word-of-mouth (eWOM) deepen the emotional connection between the brand and its audience, fostering a stronger relationship. As a result, utilizing micro-influencers on TikTok proves to be a powerful strategy that not only sustains brand existence but also broadens market reach and builds consumer loyalty in the midst of a rapidly changing digital landscape.